Trichotillomania and Dermatitis Artefacta: A Rare Coexistence - Neeraj Varyani; Sunny Garg; Garima Gupta; Shivendra Singh; Kamlakar Tripathi (Case Reports in Psychiatry)
A 24-year-old pregnant female patient presented with complains of bilateral lower limb swelling and fever for 1 month. On examination, blood pressure was 144/94 mmHg along with pitting pedal edema. She had bizarre skin lesions, aligned longitudinally and distributed over the approachable site of the body with tapering ends and in various stages of healing. Lower limbs examination also revealed similar lesions with signs of cellulitis. Her scalp had short and distorted hair suggesting pulling and plucking. These skin lesions and the denial of self-infliction by the patient made us reach the diagnosis of dermatitis artefacta with trichotillomania. Psychotherapy was advocated along with conservative management of skin lesions. The patient improved and is under our follow up.